Peran Orangtua dalam Menginternalisasi Nilai-Nilai Pendidikan Agama Kristen Bagi Remaja Di Gereja Kristus Teluk Naga - Sitompul, Lupmotis Amelia; Maya Malau; Gideon Sutrisno; Manggi, Nelci Oktavianti (Didache: Jurnal Teologi dan Pendidikan Kristen, 2024)
This study examines the role of parents in internalizing Christian religious education values ??in adolescents at the Teluk Naga Church of Christ. The main problem in this study is the less than optimal role of parents in internalizing Christian religious education values ??in adolescents, which is caused by time constraints, lack of involvement in spiritual activities, and non-open communication about spiritual issues. The purpose of the study was to describe the role of Christian parents in internalizing Christian Religious Education values, to make parents aware of their role, and to describe the church's task in equipping parents and adolescents. This study was conducted qualitatively using a case study approach. Data were collected through interviews and document analysis. This was done to gain a better understanding of the role of parents and how Christian religious education values ??are internalized. The results of the study showed that parental role models greatly influence the formation of adolescent character values ??and spirituality. Parents who are consistent in implementing Christian values ??are able to shape adolescents' mindsets, characters, and attitudes in their daily lives. However, the lack of parental involvement in spiritual activities in the church and open communication about faith makes it difficult for adolescents to internalize values. Penelitian ini mengkaji peran orangtua di dalam menginternalisasi nilai-nilai pendidikan agama Kristen pada remaja di Gereja Kristus Teluk Naga. Masalah utama dalam kajian  ini adalah kurang optimalnya peran orangtua di dalam menginternalisasi nilai-nilai pendidikan agama Kristen pada remaja, yang disebabkan oleh keterbatasan waktu, kurangnya keterlibatan dalam kegiatan kerohanian, dan komunikasi yang tidak terbuka tentang isu-isu spiritual. Tujuan penelitian untuk mendeskripsikan peran orangtua Kristen dalam penginternalisasian nilai-nilai Pendidikan Agama Kristen, menyadarkan orangtua akan perannya, serta mendeskripsikan tugas gereja dalam memperlengkapi orangtua dan remaja. Penelitian ini dilakukan secara kualitatif menggunakan pendekatan studi kasus. Data dikumpulkan melalui wawancara dan analisis dokumen. Ini dilakukan untuk mendapatkan pemahaman yang lebih baik tentang peran orangtua dan bagaimana nilai-nilai pendidikan agama Kristen diinternalisasi. Hasil penelitian menunjukkan bahwa keteladanan orangtua sangat berpengaruh pada pembentukan nilai-nilai karakter dan spiritualitas remaja. Orangtua yang konsisten dalam melakukan nilai-nilai Kristiani mampu membentuk pola pikir, karakter, dan sikap remaja dalam kehidupan sehari-sehari. Namun, kurangnya keterlibatan orangtua dalam kegiatan kerohania di gereja dan komunikasi terbuka tentang keimanan menyebabkan kesulitan bagi remaja dalam menginternalisasi nilai.